High Throughput Screening of CMAS Corrosion‐Resistant RETaO4 Based on Lamination Method - Zhilin Tian; Zhilin Chen; Shuping Wen; Wenxia Zhao; Liya Zheng; Bin Li (Advanced Science)
Abstract Rare earth tantalates (RETaO4), known for their exceptional thermomechanical properties, are promising candidates for next‐generation thermal barrier coatings (TBCs). However, the role of rare earth (RE) species in the CMAS (calcium‐magnesium‐aluminosilicate) corrosion behavior and mechanisms of RETaO4 remains unclear, hindering their design and application as TBCs. This study employs a high‐throughput approach to systematically investigate the CMAS corrosion mechanisms of RETaO4 (RE = Nd, Sm, Eu, Gd, Dy, Ho, Y, and Er) at 1300 °C. Precise analysis of the microstructure and composition reveal that the primary corrosion products are (Ca2‐xREx)(Ta2‐y‐zMgyAlz)O7 solid solutions, along with minor amounts of Ca2RE8(SiO4)6O2 apatite. These corrosion products are observed both in the recession layer and at grain boundaries. The CMAS infiltration depth of RETaO4 increases with the RE ionic radius. First‐principles calculations indicate that the formation enthalpy of corrosion products becomes more exothermic as the RE ionic radius increases, promoting the formation of corrosion products. Additionally, the wetting behavior of liquid CMAS on RETaO4 at high temperatures supports that RETaO4 with smaller RE ionic radius present better corrosion resistance. These findings provide insights into the influence of RE species on the CMAS corrosion behavior of RETaO4, offering guidelines for the rapid screening of CMAS‐resistant TBC materials.